Unilateral vocal cord adductor weakness: an atypical manifestation of motor neurone disease. Issue 2 (11th October 2021) - Yogakanthi, Saiumaeswar; Wools, Christine; Mathers, Susan
Abstract : Background: Bulbar involvement is a recognised feature of motor neuron disease/amyotrophic lateral sclerosis (MND/ALS), both as a presenting complaint and as a consequence of advancing disease. Hoarseness and dysphonia have been associated with vocal cord abductor weakness. This is usually bilateral and has also been reported as the presenting clinical feature in a handful of patients with superoxide dismutase 1 (SOD1) gene mutations. Presentation with an isolated, unilateral vocal cord adductor weakness, however, is atypical and rare. Case: In this report, we detail the case of a 38-year-old woman with dysphonia and a family history of an SOD1 mutation. Neurological features remained confined to the territory of the left vagus nerve for the next 12 months, before a more rapid rate of disease dissemination and progression. Conclusions: This case highlights the importance of recognition of vocal cord palsy as an early manifestation of MND/ALS and the critical need for monitoring to recognise potential disease progression.